Characterization of a novel antibiotic isolated from Xenorhabdus khoisanae and encapsulation of vancomycin in nanoparticles - Booysen, Elzaan (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.